1983
DOI: 10.1002/aja.1001680304
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal distribution of fiber types in the slow‐twitch soleus muscle of the C57BL/6J DY2J/DY2J dystrophic mouse during postnatal development

Abstract: The postnatal development of extrafusal fibers in the slow-twitch soleus muscle of genetically dystrophic C57BL/6J dy2J/dy2J mice and their normal age-matched controls was investigated by histochemical and quantitative methods at selected ages of 4, 8, 12, and 32 weeks. The majority of fibers in the soleus consisted of two kinds, fast-twitch oxidative-glycolytic (FOG) and slow-twitch oxidative (SO), according to reactions for alkaline-stable and acid-stable myosin ATPase and the oxidative enzyme, NADH-tetrazol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1986
1986
2002
2002

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…MEF2 activation was obvious in all the myotonic mice examined. Interestingly, MEF2 activation was limited to muscles composed mostly of fast glycolytic fibers (in wild-type mice), such as plantaris, extensor digitorum longus (EDL), and WV, but not in soleus, which has very few fast glycolytic fibers (34). MEF2 activation was observed in two strains of ADR myotonic mice: SWR/J-Clcn1 adr-mto and BALB/cByJ-Clcn1 adr-mto .…”
Section: Figurementioning
confidence: 99%
“…MEF2 activation was obvious in all the myotonic mice examined. Interestingly, MEF2 activation was limited to muscles composed mostly of fast glycolytic fibers (in wild-type mice), such as plantaris, extensor digitorum longus (EDL), and WV, but not in soleus, which has very few fast glycolytic fibers (34). MEF2 activation was observed in two strains of ADR myotonic mice: SWR/J-Clcn1 adr-mto and BALB/cByJ-Clcn1 adr-mto .…”
Section: Figurementioning
confidence: 99%
“…Since it has been shown that all the fibers of the murine soleus extend from tendon of origin to tendon of insertion, this difference could not be due to a series-connectedness of physiologically different fibers (Schwarzacher, 1957). A possible explanation arises from the evidence that the soleus is actually a mixed muscle containing both fasttwitch and slow-twitch fibers (te Kronnie et al, 1980;Ovalle et al, 1983) which are regionally concentrated. Our sampling protocol could have resulted in our analyzing different mixtures of fiber types at the insertions and origins.…”
Section: Discussionmentioning
confidence: 95%
“…Human Duchenne dystrophy and murine mdx dystrophy inherit by X chromosome-linked recessive trait and murine dy and dy 2J myopathy inherit by autosomal recessive trait. [21][22][23] It is unique that the susceptible genes for the development of the mild-moderate and progressing muscle atrophy in B rats are autosomal dominant, as in dystrophy chicken. 2 Chromosomal mappings of these loci are under way.…”
Section: Discussionmentioning
confidence: 99%